(untitled) (Revista de Ciências Agroveterinárias, 2023)
The control of Dermanyssus gallinae in small productions of laying hens is carried out by using chemical methods. However, its indiscriminate use has generated resistance and environmental pollution problems. This problem has encouraged the use of natural substances to control mites. Thus, the objective of this work was to evaluate the acaricidal activity of the bioactive citral (Ci), geraniol (Ge) and thymol (Thy) on D. gallinae under in vitro conditions using six concentrations (0.05, 1, 2, 3, 4 and 5g/mL). In addition, the interactions of the mixtures of the three bioactive were evaluated through binary (1:1) and tertiary (1:1:1) combinations. The interaction between of the combination of bioactive was performed by using CompuSyn software and calculating the combination index (CI). LC50, LC90, and LC99 with 95% confidence limits were estimated by Probit analysis. The bioactive Ci, Ge and Thy show acaricidal activity on the poultry red mite. The combination of Ge:Thy and Ci:Ge showed very strong synergism with CI of 0.084 and 0.052, whereas Ci:Thy showed strong synergism with CI of 0.122 at a concentration of 0.05g/mL. The tertiary combination in 1:1:1 showed a higher toxic effect and strong synergistic effects at low concentrations with 100% mortality at 1g/mL concentration with a CI of 0.147. The combination of natural bioactive could be an additional way to control D. gallinae without putting the welfare of the birds at risk and would be an environmentally friendly measure.